2019
DOI: 10.1126/sciadv.aav9847
|View full text |Cite
|
Sign up to set email alerts
|

Neural circuit repair by low-intensity magnetic stimulation requires cellular magnetoreceptors and specific stimulation patterns

Abstract: Although electromagnetic brain stimulation is a promising treatment in neurology and psychiatry, clinical outcomes are variable, and underlying mechanisms are ill-defined, which impedes the development of new effective stimulation protocols. Here, we show, in vivo and ex vivo, that repetitive transcranial magnetic stimulation at low-intensity (LI-rTMS) induces axon outgrowth and synaptogenesis to repair a neural circuit. This repair depends on stimulation pattern, with complex biomimetic patterns being particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 56 publications
4
71
0
1
Order By: Relevance
“…Our findings have strengthened the theories from previous studies that rTMS influences a wide variety of cells without direct activations of neuronal firing [58] including glial cells [20]. Indeed, Cullen et al showed that rTMS increases the number of newborn oligodendrocytes in the adult mouse cortex and their survival and enhances myelination [51].…”
Section: Discussionsupporting
confidence: 89%
“…Our findings have strengthened the theories from previous studies that rTMS influences a wide variety of cells without direct activations of neuronal firing [58] including glial cells [20]. Indeed, Cullen et al showed that rTMS increases the number of newborn oligodendrocytes in the adult mouse cortex and their survival and enhances myelination [51].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, some recent experiments revealed that radical pair formation in the mammalian-type CRYs can occurs during magnetosensitivity by molecular oxygen and is not dependent to light [60][61][62] . CRYs can implicate to reinnervation and repairing of nervous systems in the mammalian brain as light-independent magnetosensor by an external low intensity EMF stimulations 63 . However, magnetosensitivity property requires the light in the ies, birds, etc.…”
Section: Discussionmentioning
confidence: 99%
“…MFs exposure on the cell behaviors and neural activities 63,69 . Redox cycling of CRYs participates the formation of radical pair and singlet/triplet interconversion in the FAD¯° that triggers the transfer electron form CRYs to MagR and magnetic susceptibility in MagR proteins 16 .…”
Section: Studies Have Shown That the Overexpression Of Crys In Numeromentioning
confidence: 99%
“…There is evidence that LIMS can modulate brain function in humans [12] and in animal models [24]; however, the cellular and molecular mechanisms underlying the therapeutic effects of LIMS remain poorly understood. A few in vitro and ex vivo studies have demonstrated that LIMS alters gene expression [25], intracellular calcium concentrations in non-neuronal cells [26] [27] [28] and neuronal cells [29], neurobiological changes [30], neuronal excitability [31], and cellular metabolic and biochemical profiles [32]. However, it is still unknown whether LIMS provides facilitation or suppression effects depending on the stimulation protocol.…”
Section: Introductionmentioning
confidence: 99%